PENGARUH PENERAPAN GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN YANG TERINDEKS DI IDX80: PENGARUH PENERAPAN GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN YANG TERINDEKS DI IDX80 - Annisya Fitri Khairina P; Musdalifah Siti (Pusat P2M Politeknik Negeri Batam, 2025)
Increasing environmental concerns and the urgency to achieve sustainability have prompted companies to strengthen their environmental impact mitigation and enhance transparency. However, the profitability of several LQ45 companies declined in 2023. The inconsistency of literature findings regarding the influence of Green accounting, environmental performance, and liquidity on profitability is a core issue. The objective of this research is to analyze how the implementation of green accounting, environmental performance, and liquidity affects the profitability of companies indexed in IDX80 during the 2019-2023 period. The research method used is panel data regression analysis, with data processed using Eviews 13 software. The study's findings reveal that green accounting does not have a positive effect on profitability. Conversely, environmental performance and liquidity are found to have a positive effect on profitability. Theoretically, this study enriches the literature on the relationship between environmental practices, liquidity, and financial performance in the Indonesian capital market. Practically, company management can use these findings as a guide to improve environmental performance and manage liquidity for profitability and competitiveness. Investors are advised to consider environmental performance as a key determinant in investment decisions, and regulators can evaluate green accounting policies to encourage more tangible financial impacts.